The Determinants And Consequences Of Green Innovation - Haliza Nurlarasati (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of green accounting and green intellectual capital on green innovation in energy companies listed on the Indonesia Stock Exchange during 2022–2024. Using purposive sampling, 207 firm-year observations were analyzed through multiple linear regression. The findings show that green accounting and green intellectual capital have a positive and significant effect on green innovation. These results indicate that stronger environmental accounting practices and green knowledge resources enhance firms’ capability to develop sustainable innovation. This study implies that energy companies should strengthen sustainability-oriented internal systems and intellectual resources to support long-term competitiveness and environmental responsibility. Keywords: Green Accounting, Green Intellectual Capital, Green Innovation, Firm Size, Firm Performance, Energy Sector, Sustainability Reporting, Indonesia